Human Adult Stem Cells Maintain a Constant Phenotype Profile Irrespective of Their Origin, Basal Media, and Long Term Cultures - Indumathi Somasundaram; Rashmi Mishra; Harikrishnan Radhakrishnan; Rajkumar Sankaran; Venkata Naga Srikanth Garikipati; Dhanasekaran Marappagounder (Hindawi Limited, 2015)
The study aims to identify the phenotypic marker expressions of different human adult stem cells derived from, namely, bone marrow, subcutaneous fat, and omentum fat, cultured in different media, namely, DMEM-Low Glucose, Alpha-MEM, DMEM-F12 and DMEM-KO and under long term culture conditions (>P20). We characterized immunophenotype by using various hematopoietic, mesenchymal, endothelial markers, and cell adhesion molecules in the long term cultures (Passages-P1, P3, P5, P9, P12, P15, and P20.) Interestingly, data revealed similar marker expression profiles irrespective of source, basal media, and extensive culturing. This demonstrates that all adult stem cell sources mentioned in this study share similar phenotypic marker and all media seem appropriate for culturing these sources. However, a disparity was observed in the markers such as CD49d, CD54, CD117, CD29, and CD106, thereby warranting further research on these markers. Besides the aforesaid objective, it is understood from the study that immunophenotyping acts as a valuable tool to identify inherent property of each cell, thereby leading to a valuable cell based therapy.